2000
DOI: 10.2136/sssaj2000.642460x
|View full text |Cite
|
Sign up to set email alerts
|

Infiltration in Homogeneous Sands and a Mechanistic Model of Unstable Flow

Abstract: One‐dimensional infiltration experiments were conducted to study the mechanics of unstable flow in homogeneous soils under non‐ponding infiltration. A mechanistic model is presented which explains soil water pressure gradients that are characteristic of stable and unstable flow in homogeneous soils and is based on a dynamic soil water entry pressure, the Darcy‐Buckingham flux equation, and hysteretic moisture retention functions. Infiltration experiments were conducted with five sand samples under applied flux… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
126
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 90 publications
(132 citation statements)
references
References 31 publications
6
126
0
Order By: Relevance
“…The occurrence of a drainage process, such as a q-bump profile, is known or expected to occur in fingers emerging during infiltration in a horizontally extended column [Glass et al, 1989;Baker and Hillel, 1988;Selker et al, 1992b;Cho and de Rooij, 1999;Kawamoto and Miyazaki, 1999]. However, our experiment, along with the experiment by Geiger and Durnford [2000] where water pressure is measured, showed that it is not a special phenomenon restricted to finger columns that are surrounded by dry media in a two-or three-dimensional flow field, but are a more common phenomenon seen even in one-dimensional infiltration. The saturated wetting front advance is a physical property of the dry granular medium having a narrow particle size distribution, which is not conditioned by any special boundary condition.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…The occurrence of a drainage process, such as a q-bump profile, is known or expected to occur in fingers emerging during infiltration in a horizontally extended column [Glass et al, 1989;Baker and Hillel, 1988;Selker et al, 1992b;Cho and de Rooij, 1999;Kawamoto and Miyazaki, 1999]. However, our experiment, along with the experiment by Geiger and Durnford [2000] where water pressure is measured, showed that it is not a special phenomenon restricted to finger columns that are surrounded by dry media in a two-or three-dimensional flow field, but are a more common phenomenon seen even in one-dimensional infiltration. The saturated wetting front advance is a physical property of the dry granular medium having a narrow particle size distribution, which is not conditioned by any special boundary condition.…”
Section: Discussionmentioning
confidence: 76%
“…If a drainage process is to occur, the water content right behind the wetting front needs to be almost saturated, and it decreases upward until a value is reached such that the hydraulic conductivity equals the applied water flux. Such water content profiles with q-bumps (or nonmonotonic profiles) at the wetting front are expected based on studies on finger structures [Glass et al, 1989;Selker et al, 1992bSelker et al, , 1992c and especially from pressure histories measured during 1-D infiltration into a material that exhibits fingering [Geiger and Durnford, 2000]. However, such profiles are not expected from the general theory of water flow in unsaturated porous media that is based on equation (1).…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…In Richards' theory, the pressure head y is assumed to be in equilibrium and to depend on q, y = y eq (q) (neglecting capillary hysteresis). [7] We are inspired by a model for dynamic capillary pressure at a wetting front that Hsu and Hilpert [2011] recently incorporated into the GA model for water infiltration and that is supported by various Darcy-scale infiltration experiments [Weitz et al, 1987;Geiger and Durnford, 2000;DiCarlo, 2004;Annaka and Hanayama, 2005]:…”
Section: Theorymentioning
confidence: 99%
“…[17] To arrive at a parameterization for the nonequilibrium capillary pressure given by equation (4), we built on a parameterization of dynamic capillary pressure at an infiltration front that was recently developed [Hsu and Hilpert, 2011] based on an analysis of water-infiltration experiments into dry porous media [Geiger and Durnford, 2000]:…”
Section: Simulationsmentioning
confidence: 99%